Toleransi Di Kalangan Santri Pondok Pesantren Kabupaten Bekasi - Nafiuddin Nafiuddin; Dewi Maharani (Refleksi: Jurnal Kajian Agama dan Filsafat, 2024)
Tolerance is the most important element in religious moderation when compared to other dimensions. Several phenomena of intolerance and radicalization emerged in Bekasi Regency, such as the arrest of terrorists, rejection of the establishment of places of worship for adherents of other religions, and so on. This makes the role of Islamic boarding schools very important in stemming intolerant movements. This research is quantitative. The sampling method used in this research is the Purposive Sampling and Quota Sampling method. The Purposive Sampling method was used in selecting two Islamic boarding schools in Bekasi Regency, namely YAPINK and Attaqwa, while the Quota Sampling method was used in distributing the selected sample of students. The number of samples used in this research was 312 students. The results of this research are that the contribution of tolerance is very significant in instilling religious moderation, then Islamic boarding school students have moderate views and attitudes in the dimension of tolerance.